2022
DOI: 10.53730/ijhs.v6ns9.12434
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between oxidative stress and clopidogrel drug in Iraqi patients with coronary artery disease

Abstract: Background: Coronary Artery Disease (CAD) is one of the largest causes of mortality worldwide. Clopidogrel, antiplatelet drug, has been widely used for management of CAD. The current study aimed to investigate the effect of clopidogrel on the oxidative stress in CAD patients. Methods: One hundred CAD patients, who were followed-up for 5 days after receiving clopidogrel, and 50 healthy volunteers were included in this study. Parameters include catalase (CAT), total antioxidant capacity (TAC), total oxidant capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…It is usually used as an indicator for oxidative stress in many diseases. Several studies reported that oxidative stress contributes in the antioxidant reduction and the development of many diseases [36][37][38][39][40][41][42]. It has been reported that TAM induces the oxidative stress generation [43].…”
Section: Resultsmentioning
confidence: 99%
“…It is usually used as an indicator for oxidative stress in many diseases. Several studies reported that oxidative stress contributes in the antioxidant reduction and the development of many diseases [36][37][38][39][40][41][42]. It has been reported that TAM induces the oxidative stress generation [43].…”
Section: Resultsmentioning
confidence: 99%